Implicit and Explicit Routes to Recognize the Own Body: Evidence from Brain Damaged Patients - Candini, Michela; Farinelli, Marina; Ferri, Francesca; Avanzi, Stefano; Cevolani, Daniela; Gallese, Vittorio; Northoff, Georg; Frassinetti, Francesca (Frontiers in Human Neuroscience, 2016)
Much research suggested that recognizing our own body-parts and attributing a body-part to our physical self likely involve distinct processes. Accordingly, facilitation for self body-parts was found when an implicit, but not an explicit, self-recognition was required. Here, we assess whether implicit and explicit bodily self-recognition is mediated by different cerebral networks and can be selectively impaired after brain lesion. To this aim, right- (RBD) and left- (LBD) brain damaged patients and age-matched controls were presented with rotated pictures of either self- or other-people hands. In the Implicit task participants were submitted to hand laterality judgements. In the Explicit task they had to judge whether the hand belonged, or not, to them. In the Implicit task, controls and LBD patients, but not RBD patients, showed an advantage for self body stimuli. In the Explicit task a disadvantage emerged for self compared to others’ body stimuli in controls as well as in patients. Moreover, when we directly compared the performance of patients and controls, we found RBD, but not LBD, patients to be impaired in both the implicit and explicit recognition of self body-part stimuli. Conversely, no differences were found for others’ body-part stimuli. Crucially 40% RBD patients showed a selective deficit for implicit processing of self body-part stimuli, whereas 27% of them showed a selective deficit in the explicit recognition of their own body. Additionally, we provide anatomical evidence revealing the neural basis of this dissociation. Based on both behavioral and anatomical data, we suggest that different areas of the right hemisphere underpin implicit and explicit self body knowledge.